Analysis of the Role of Customer Reviews and Product Ratings in Building Brand Trust and Loyalty on the Shopee Barokah Platform - Mochammad Adittya Mahendra; Ahmad Mahfud; Moh Aminullah; Melyna Mustika Rini; Afaful Ummah (Penerbit Hellow Pustaka, 2026)
This study applies a Systematic Literature Review (SLR) using a descriptive qualitative approach to analyze the role of customer reviews and product ratings in building brand trust and their impact on customer loyalty within the Shopee Barokah platform. The review draws on previous empirical studies compiled in the referenced document. The findings indicate that review quality, reviewer credibility, and rating consistency significantly contribute to the formation of brand trust. Brand trust functions as a key mediator linking customer reviews and product ratings to customer loyalty. The results emphasize that reviews and ratings do not directly generate loyalty but operate through trust formation. The study also identifies research gaps related to consumer psychological mechanisms, the Islamic value context of Shopee Barokah, and the depth of review content quality for further exploration.